Conflicting and Changing Health Recommendations and Their Influence on Cancer Prevention: Social Media Use and Trust as Positive Mediators - Bruns, Mary; Kim, Soojung Gina (American journal of health promotion, 2025)
Purpose This study examines the mediating roles of social media use and trust in the relationship between experts’ health recommendations being conflicting and changing and their intention to receive cancer screening tests using the O1-S-O2-R model. Design Cross-sectional. Setting Data were extracted from the Health Information National Trends Survey (HINTS) 6. Subjects Of 6252 individuals, 5014 were used in the final analysis. The total weighted sample size is 255,489,241. Measures Conflicting & Changing Health Recommendations (O 1 ): How often experts’ health recommendations seem to conflict and change. Social Media Use (S): The use of social media to seek and share health information. Trust in Cancer Information (O 2 ): Trust in cancer information from doctors, government health agencies, and scientists. Interest in Cancer Screening in the next year (R). Analysis Multiple and logistic regressions were performed with the weighted sample. A PROCESS mediation model with a 5000 bootstrapping sample was also performed. Results The perception of health recommendations from experts conflicting was a positive, marginally significant predictor of social media use for seeking and sharing health information (P = .08), which generated higher trust in cancer information from government health agencies (P < .05) and higher intention to receive cancer screening tests within the next year (P < .01). Conclusions With strong digital health literacy and appropriate social media algorithms, social media could reinforce cancer screening behaviors.